Treatment of ischemic stroke with r-tPA: implementation challenges in a tertiary hospital in Brazil - Elza Dias Tosta (Arquivos de Neuro-Psiquiatria, 2014)
Purpose: This paper presents the initial experience with thrombolysis for acute ischaemic stroke at Hospital de Base do Distrito Federal (HBDF), Brazil, and the difficulties associated with the implementation of this treatment. Method: A retrospective study was performed using the medical records of all patients with acute stroke who were treated with intravenous alteplase in our department, between May 2011 and April 2012. Results: The thrombolytic therapy was administered to 32 patients. The mean time between the ictus and the start of stroke therapy start was 195 (60-270) minutes. Sixteen patients demonstrated a significant clinical improvement (decrease in National Institute Health Stroke Scale [NIHSS] score≥4 points in 24 hours); 6 patients were discharged with an NIHSS score of 0 and 2 demonstrated haemorrhagic transformation. Conclusions: The results of our study are similar to those reported in the literature, although we have been dealing with difficulties, such as the lack of a stroke unit.